As relações comerciais entre o Brasil e a zona do euro, de 2001- 2016: Uma análise da complexidade econômica - NUNES, Rodolfo Francisco Soares (2020)
With a focus on the Economic Complexity of trade between Brazil and the Eurozone, from 2001-2016, this paper aims to emphasize the influence of this trade on the overall picture of the economic complexity of the Brazilian export agenda. Through data obtained from the official foreign trade database of Brazil and related to the Atlas of Economic Complexity data, there was a decrease in the Product Complexity Index of products exported by Brazil to the Eurozone, but this decrease only accentuates a structural framework of the Brazilian export agenda and its productive structure. Moreover, in the light of the traditional theories and the new theories of international trade, such trade relationship is subject to analysis and highlighting some other points, such as distance and transportation, variables that are not understood by Economic Complexity. Although trade with the Eurozone has lost complexity, it is still one of Brazil's main trading partners, despite its relative decreasing relevance over the period, largely due to the reorganization of the World Economic Order.